The Development of Education Character Policy and Programs in Information Society of Kampung Cyber Yogyakarta - Muhammad Amirrudin; Harun Harun; Muhammad Yasid; Surur Roiqoh; Fatkhul Sani Rohana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This ariticle presents studies about the Strengthening Character Education policy and practised in Kampung Cyber Yogyakarta's information society. The aim of this research was to describe how character education policy materializes in Kampung Cyber community's efforts in developing character education programs. The research was a qualitative research with a case study approach. The data were obtained through interviews, observation and documentation in the field directly. The results were divided into two things according to the main study. First, related to the dimensions and second related to the results of character education development in Kampung Cyber. The results show that the development of character education in Kampung Cyber covered five primary characters and targeted three fundamental problems: foundational problems, structural problems and operational problems. In general, the product of character education in Kampung Cyber was positive, because they can increase social-communal awareness, improve religious practice, and the synergy of character education and its natural habituation. Keywords: Education Character Policy, Strengthening Education Character